Harapan akan Keadilan - Wulandari, Maria Veronica Endah (Lux et Sal, 2025)
Each individual in every age lives with a perpetual hope for the realization of justice or iustitia in this world, because justice is closely related to relations between humans. The purpose of the law itself is to realize the hope for justice so that humans can live in brotherhood with harmony. However, the application of rigid laws may cause injustice. This article attempts to deepen the understanding of justice as a virtue supported by other virtues: misericordia, caritas, aequitas and veritas. The balancing elements and pointers towards true justice, as the hope of all humans, especially in this Jubilee Year.